Pushed for time or saving on fuel: fine-scale energy budgets shed light on currencies in a diving bird - Rory Wilson (Proceedings of the Royal Society B: Biological Sciences, 2009)
Shepard ELC, Wilson RP, Quintana F, Gómez Laich A, Forman D (2009) Pushed for time or saving on fuel: fine scale energy budgets shed light on currencies in a diving bird. Proceedings of the Royal Society B 276:3149-3155.